2008
DOI: 10.1002/lt.21627
|View full text |Cite
|
Sign up to set email alerts
|

Decline in native kidney function in liver transplant recipients is not associated with BK virus infection

Abstract: BK virus (BKV) infection is an established cause of allograft dysfunction in renal transplant recipients. The relationship between BKV infection and chronic kidney disease (CKD) post-orthotopic liver transplantation (OLT) is not well understood. This study aimed to determine the prevalence of BKV infection, its relationship to CKD and renal function loss over time in patients receiving OLT. Prevalence of BK viruria and viremia were studied in 41 post-OLT patients after a mean 6.5 Ϯ 4.7 years posttransplantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Higher prevalence of BKV viruria in this study compared with that reported in other studies may be attributed to higher dosages of immunosuppressants used in the first three months after liver transplantation, leading to more intensive immunosuppression in our subjects. Despite high prevalence of BKV viruria in liver transplant recipients, the renal outcome seems unassociated with the presence of BKV viruria5825. Similarly, our data also demonstrated that eGFR was not significantly different in the high and low urinary BKV load groups except for the 2 nd and 3 rd months.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Higher prevalence of BKV viruria in this study compared with that reported in other studies may be attributed to higher dosages of immunosuppressants used in the first three months after liver transplantation, leading to more intensive immunosuppression in our subjects. Despite high prevalence of BKV viruria in liver transplant recipients, the renal outcome seems unassociated with the presence of BKV viruria5825. Similarly, our data also demonstrated that eGFR was not significantly different in the high and low urinary BKV load groups except for the 2 nd and 3 rd months.…”
Section: Discussionsupporting
confidence: 66%
“…observed in a prospective study that persistent BKV viremia might be related to the impaired renal function in liver transplant recipients5. In contrast, other studies did not discover the association between BKV viremia and viruria with renal dysfunction in liver transplant patients678. The discrepancy in high association of BKV infection with renal allograft function in renal transplant recipients and no obviously causal relationship between BKV infection and renal function in liver transplant recipients may highlight the importance of the second hit such as ischemia or inflammation in the development of renal dysfunction in addition to BKV infection.…”
mentioning
confidence: 98%
“…Clinical impact is relevant, as loss of the renal graft ranges from 30% up to > 80% of cases [12][13][14] ; in transplant centres where screening for polyomavirus replication in the urine and plasma is performed, the rate of graft loss is lower [15] . Several studies evidenced that BK viremia is only rarely observed in non-kidney solid organ transplant recipients and biopsy-confirmed cases of nephropathy have been described in few case reports [16][17][18][19][20][21][22] , despite the similar or even higher level of immunosuppression, thus supporting the role of organ determinants in the pathogenesis of PVAN.…”
Section: Human Polyomaviruses and Nephropahtymentioning
confidence: 99%
“…However, the fact that decoy cells also may emerge in other virus infections (John Cunningham virus, Simian virus 40, cytomegalovirus, adenovirus), 28 and that they may be discharged with urine in asymptomatic individuals and may be detected in urine in the presence of malignity, 29 renders its value questionable in diagnosing BK virus nephritis. This is supported by the fact that Salama and associates, 30 in their study comprising only liver transplant recipients, reported finding decoy cells in 9.7% of the patients without detecting viruria in any of them. Because BK virus may be discharged in urine in asymptomatic individuals even if nephritis is not clinically present, no matter which method is used for screening, the diagnostic value of viruria in urine is lower than that of BK viremia in diagnosing BK virus infection.…”
Section: Discussionmentioning
confidence: 73%